Chemosensitization as a Means to Augment Commercial Antifungal Agents - Campbell, Bruce C.; Chan, Kathleen L.; Kim, Jong H. (Frontiers in Microbiology, 2012)
Antimycotic chemosensitization and its mode of action are of growing interest. Currently, use of antifungal agents in agriculture and medicine has a number of obstacles. Foremost of these is development of resistance or cross-resistance to one or more antifungal agents. The generally high expense and negative impact, or side effects, associated with antifungal agents are two further issues of concern. Collectively, these problems are exacerbated by efforts to control resistant strains, which can evolve into a treadmill of higher dosages for longer periods. This cycle in turn, inflates cost of treatment, dramatically. A further problem is stagnation in development of new and effective antifungal agents, especially for human chemotherapy. Efforts to overcome some of these issues have involved using combinations of available antimycotics (e.g., combination therapy for invasive mycoses). However, this approach has had inconsistent success and is often associated with a marked increase in negative side effects. Chemosensitization by natural compounds to increase effectiveness of commercial antimycotics is a somewhat new approach to dealing with the aforementioned problems. The potential for safe natural products to improve antifungal activity has been observed for over three decades. Chemosensitizing agents possess antifungal activity, but at insufficient levels to serve as antimycotics, alone. Their main function is to disrupt fungal stress response, destabilize the structural integrity of cellular and vacuolar membranes or stimulate production of reactive oxygen species, augmenting oxidative stress and apoptosis. Use of safe chemosensitizing agents has potential benefit to both agriculture and medicine. When co-applied with a commercial antifungal agent, an additive or synergistic interaction may occur, augmenting antifungal efficacy. This augmentation, in turn, lowers effective dosages, costs, negative side effects and, in some cases, countermands resistance.